2023
DOI: 10.3390/molecules28062837
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Edible Mushrooms for Diabetes: Unveiling Their Role in Prevention and Treatment

Abstract: Diabetes mellitus is a complex illness in which the body does not create enough insulin to control blood glucose levels. Worldwide, this disease is life-threatening and requires low-cost, side-effect-free medicine. Due to adverse effects, many synthetic hypoglycemic medications for diabetes fail. Mushrooms are known to contain natural bioactive components that may be anti-diabetic; thus, scientists are now targeting them. Mushroom extracts, which improve immune function and fight cancer, are becoming more popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 146 publications
0
3
0
Order By: Relevance
“…It also reduces cancer risk, especially breast and colon cancer where the gut bacteria play intermediary roles between the disease and its risk factors (88)(89)(90). The fiber content helps to lower blood sugar levels, making it highly beneficial for management of diabetes and numerous sugar related diseases (91). The fiber present in Pleurotus ostreatus also aids in increasing digestion and excretion by contributing to stool weight and reducing transit time.…”
Section: Pleurotus Ostreatus As a Functional Foodmentioning
confidence: 99%
“…It also reduces cancer risk, especially breast and colon cancer where the gut bacteria play intermediary roles between the disease and its risk factors (88)(89)(90). The fiber content helps to lower blood sugar levels, making it highly beneficial for management of diabetes and numerous sugar related diseases (91). The fiber present in Pleurotus ostreatus also aids in increasing digestion and excretion by contributing to stool weight and reducing transit time.…”
Section: Pleurotus Ostreatus As a Functional Foodmentioning
confidence: 99%
“…67 There are proteins from sources which have been evaluated at in vitro levels, but no clinical trials regarding the specific role of their protein were found, such as fungi. 68 It is expected that clinical trials employing alternative proteins will be carried out soon and will pave the way to employ these protein sources as ingredients in the food industry. Promoting the use of alternative protein sources can contribute to the achievement of Sustainable Development Goals (SDGs), in particular the zero hunger goal (SDG 2) aiming to end hunger ensuring food safety, while taking advantage of environmentally friendly sources or using food waste as a source of dietary compounds (SDG 13-climate change or SDG 15-terrestrial ecosystems, forestry, and biodiversity).…”
Section: Food and Functionmentioning
confidence: 99%
“…Lipid peroxides were analyzed using the thiobarbituric acid reactive substances method [24], and the results were expressed in nmol of malondialdehyde (MDA) per mL of plasma. Carbonylated proteins, resulting from the interaction between reactive oxygen species and proteins, were evaluated in the plasma using the guanidine hydrochloride method [25], with the results expressed in nmol per milligram of protein.…”
Section: Assessment Of Oxidative Stress In Rat Plasmamentioning
confidence: 99%